KONDISI PENDUKUNG SISWA BELAJAR: Conditions Supporting Student Learning - Hani’ah, Munnal; Wangid, Muhammad Nur (Anterior Jurnal, 2024)
Student conditions are students’ circumstances or situations that can influence the learning process and outcomes. These conditions are divided into two, namely internal conditions (which exist within the student) and external conditions (which exist outside the student). The student’s condition influences the presence of student motivation in learning or the presence of learning difficulties. The aim of this research is to describe the conditions that support students’ learning. To achieve research objectives, this research uses library and documentary research methods. Some conditions that support students’ learning are learning in a pleasant atmosphere; paying attention to students’ emotions; determining teaching materials and curriculum that suit student needs; teacher as a support system; conducive learning environment; as well as learning facilities and infrastructure. With these various supporting conditions, students will obtain maximum and optimal learning outcomes.